Madhyamika Bakyarana, Class-X - (:unkn) unknown (Board of Secondary Education Odisha, 2022)
This is Odia grammar book for class-10.
Keywords: Odia; Madhyamika Bakyarana; Class-X; Odia Grammar; Odia; Odia